1997
DOI: 10.1021/jp971692p
|View full text |Cite
|
Sign up to set email alerts
|

Interactions and Molecular Weights of Simple Micelles and Mixed Micelles in Taurocholate and Taurocholate−Lecithin Solutions

Abstract: A quasielastic light-scattering (QLS) technique was employed to investigate simple micelles and mixed micelles formed in taurocholate (TC) and TC-lecithin (L) solutions. When the size and polydispersity of simple TC micelles were nearly unchanged with total TC concentrations, the simple TC micelles were suggested to be all of a single size. According to the relationship between the total TC concentration and the TC monomer concentration, a monomer-micelle model predicted the aggregation number (n) and the crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
43
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(52 citation statements)
references
References 25 publications
7
43
2
Order By: Relevance
“…Moreover, the (bile salt + protein) interactions in entero-hepatic and gallbladder bile are significant examples of (surfactant + protein) interactions that play a key role in biochemically relevant processes [20]. In spite of this, not much is known about the details of (bile salt + protein) aggregates, especially by taking amino acids as model compounds [21][22][23] and studies on the mono-dispersity [24] and poly-dispersity [25][26][27][28] of bile salt aggregates have remained a matter of controversy.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the (bile salt + protein) interactions in entero-hepatic and gallbladder bile are significant examples of (surfactant + protein) interactions that play a key role in biochemically relevant processes [20]. In spite of this, not much is known about the details of (bile salt + protein) aggregates, especially by taking amino acids as model compounds [21][22][23] and studies on the mono-dispersity [24] and poly-dispersity [25][26][27][28] of bile salt aggregates have remained a matter of controversy.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] In both cases, there is an initial formation of small aggregates driven by the hydrophobic interaction between the apolar faces of the rings of two molecules (back-to-back aggregation). Literature shows a great variety of the CMCs values 6,10,11,[14][15][16][17][18] that can be explained either by the slow change of the successive aggregation steps or by the experimental constraints. Regarding CHAPSO and CHAPS, literature about their aggregation properties is scarce, and it is basically centered on CHAPS.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, Liu et al suggested a constant size of simple TC micelles and a monomer-micelle model for the formation of simple TC micelles due to the hydrophobic interaction of TC monomers. 7,8 Based on this model, the relationship between monomer TC concentrations (C 1 ) and total TC concentrations (C), determined using the Sephadex G-10 bead uptake method, could be fitted by a least-squares technique. [8][9][10] In addition, the aggregation number (n) and the critical micelle concentration (CMC) were estimated to be~5 and~10 mM.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Based on this model, the relationship between monomer TC concentrations (C 1 ) and total TC concentrations (C), determined using the Sephadex G-10 bead uptake method, could be fitted by a least-squares technique. [8][9][10] In addition, the aggregation number (n) and the critical micelle concentration (CMC) were estimated to be~5 and~10 mM. 8 However, the estimated value of CMC (~10 mM) 8 was higher than the reported value (~6 mM) of CMC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation